The effect of summer jobs on post-schooling incomes - Moudud Alam; Kenneth Carling; Ola Nääs (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
In part because of high youth unemployment, students' transition from school to work is an important policy and research topic. Public programs offering summer jobs or work while in high school as measures to smooth the transition is commonplace. The immediate effect of the programs on school attendance, school grades, and disposable income is well documented. However, their effect on the transition to the labor market remains unsettled, partly because of a potential selection bias in previous observational studies. In this paper, 2650 first graders of high school in Falun Council, Sweden, randomly allotted summer jobs via a program in the years of 1997-2003, are followed ten years after graduation. The program led to a substantially larger accumulation of work experience while in high school for offered (particularly weak academically performing) females, but not for offered males. Hence, the immediate program effect was heterogeneous. Females were used to estimate the causal effect of work experience while in high school on post-schooling incomes. The (statistically) significant estimate implies an elasticity of 0.4. Work experience while in high school seems to be of future benefit, but the elasticity is potentially inflated due to heterogeneous effects that we were unable to account for.
Keywords: C93; J24; J68; 330; experimental data; work experience; work while in school; selection bias